Semiotika Tampilan Kaum Pribumi pada Film Pengepungan di Bukit Duri - Anggiena Nattaly; Fajriannoor Fanani (CV. ITTC INDONESIA, 2025)
This study is motivated by the increasing representation of social conflicts and ethnic identities in Indonesian cinema, which often portrays particular stereotypes toward certain social groups. Pengepungan di Bukit Duri (2025), directed by Joko Anwar, was selected as the object of this research because it depicts open acts of violence committed by the indigenous majority against the Chinese ethnic community, while also illustrating the ideological repositioning of the majority group within national cinema. The main problem of this research is how the film represents power, identity, and violence through a system of visual signs. The purpose of this study is to interpret how the film constructs representations of power, identity, and violence through visual semiotic systems, and to emphasize the importance of understanding cinema as an ideological space that shapes Indonesian society’s perceptions of the relationship between majority and minority groups. This research employs a qualitative method with a descriptive design, using Roland Barthes’s semiotic approach combined with Pierre Bourdieu’s theory of symbolic power. The analysis is conducted interpretatively on gestures, facial expressions, lighting, camera composition, and visual symbols appearing in key scenes. The results show that the film portrays the indigenous majority as perpetrators of violence in a way that normalizes symbolic domination through visual narrative. Elements such as dark lighting, low-angle shots, and graffiti symbols are used to reinforce the ideological opposition between majority and minority groups. The myth analysis reveals that the film constructs an ideology of violence as an inherent trait of the indigenous population, thereby potentially strengthening social stereotypes. Thus, Pengepungan di Bukit Duri functions not only as a cinematic work but also as a cultural text that articulates and reinforces the ideology of power in contemporary Indonesian society.